PP.16.06: RESISTIN, BLOOD PRESSURE AND CARDIOVASCULAR EVENTS. (June 2015) - Rodríguez, I. Marcelino; Rodríguez, C.; Gannar, F.; Brito, B.; Almeida, D.; Alemán, J.; Domínguez, S.; León, A. Cabrera De
Abstract : Objective: Resistin is mainly a cytokine in human, but an adipokine in mice. We explored the association between serum resistin, blood pressure, hypertension, and cardiovascular events in the general population. Design and method: A follow-up study of 6636 adults, randomly recruited from the general population, during 3, 5 years. Incidence of cardiovascular and cerebrovascular events was registered. In addition to serum resistin and blood pressure, we measured cardiovascular risk factors: age, gender, smoking, diabetes, insulin resistance, serum lipids, intake of sodium, cafe, alcohol and saturated fat, obesity, and physical activity. The resistin-blood pressure bivariate associations were adjusted for the measured risk factors with multivariate regression models. Cox models were adjusted for the vascular events incidence. Results: Systolic and diastolic blood pressure showed an inverse correlation with resistin (-0, 048, p < 0, 001; -0, 067, p < 0, 001). Individuals above the 80 percentile of resistin had an inverse association with hypertension (OR = 0, 712 CI95% = 0, 624–0, 813; p < 0, 001). Multivariate analysis corroborated these results. Cox models showed the higher incidence of acute myocardial infarction in the resistin 80 percentile subgroup (RR = 2, 632; CI95% = 1, 303–5, 317; p = 0, 007), but not difference for cerebrovascular events. Conclusions: In spite of resistin has an inverse association with blood pressure and hypertension, this cytokine is a risk factor for cardiovascular events